Lower Eyelid Reconstruction: A New Classification Incorporating the Vertical Dimension. Issue 2 (August 2019) - Alghoul, Mohammed S.; Bricker, Jonathan T.; Vaca, Elbert E.; Purnell, Chad A.
Abstract : Background: Lower eyelid defects are traditionally classified based on depth and 25 percent increments in defect width. The authors propose a new classification system that includes the vertical defect component to predict functional and aesthetic outcomes. Methods: A retrospective review of patients who underwent lower lid reconstruction performed by a single surgeon was performed. Defects were classified into four categories based on the vertical component: (1) pretarsal; (2) preseptal; (3) eyelid-cheek junction; and (4) complex pretarsal/preseptal. Preoperative and postoperative central and lateral marginal reflex distance-2 values were obtained. Aesthetic outcomes were evaluated by three blinded reviewers. Outcomes were compared using one-way analysis of variance and analysis of covariance with Bonferroni corrected post hoc comparisons to control for defect area and width. Results: Thirty-four patients underwent reconstruction of lower eyelid defects. There were 12 pretarsal defects (type I), nine preseptal defects (type II), nine eyelid-cheek defects (type III), and four complex pretarsal/preseptal defects (type IV). Postoperative retraction was highest in the complex pretarsal/preseptal group at 75 percent, with a significantly greater change from preoperative to postoperative central and lateral marginal reflex distance-2 compared with the other groups ( p < 0.01) and worse postoperative mean aesthetic scores ( p < 0.001). Type IV patients had significantly more revision operations (mean, 5.5) compared with the other groups ( p < 0.001). Conclusions: The vertical dimension of lower eyelid defects is an important variable. A new classification system is proposed that supplements width-based methods for improved surgical planning and prediction of postoperative outcomes in lower eyelid reconstruction. CLINICAL QUESTION/LEEVL OF EVIDENCE: Therapeutic, IV. Abstract : Supplemental Digital Content is available in the text.